KARAKTERISTIK DAN VARIABILITAS BULANAN ANGIN PERMUKAAN DI PERAIRAN SAMUDERA HINDIA - Martono, Martono (Makara Journal of Science, 2009)
Monthly Characteristic and Variability of Surface Wind Over the Indian Ocean. This research was conducted to understand monthly characteristic and variability of surface wind circulation over the Indian Ocean. The method used in this research was descriptive analysis. The data used was the monthly direction and velocity of surface wind obtained from the National Oceanic and Atmospheric Administration. The result showed that the monthly variability of surface wind circulation over the Indian Ocean is influenced by movement of the sun. The change in the variability of surface wind circulation was more in the northern hemisphere, but vice versa surface wind circulation in the southern hemisphere was constant during the year. Generally, velocity of surface wind circulation was the greatest occurred in July and was the weakness occurred in April.